Diverging Stories of “Missing Women” in South Asia: Is Son Preference Weakening in Bangladesh? - Kabeer, Naila; Huq, Lopita; Mahmud, Simeen (Routledge, 2016)
This article was published in the Journal of Feminist Economics [ © 2013 IAFFE ] and the definite version is available at: https://doi.org/10.1080/13545701.2013.857423 The book chapter's website is at: http://www.tandfonline.com/doi/abs/10.1080/13545701.2013.857423